Values and job expectations of english and chinese-educated in Singapore. - Chua, Wan Xuan. (2008)
This is a comparative study between the English and Chinese-educated in Singapore to identify differences in value priorities, differences in job expectations and explore the relationship between the values individuals hold and the expectations they have of a job and the organisation they work in.